Answer:
Simplifying
44 = 2(3x + -5)
Reorder the terms:
44 = 2(-5 + 3x)
44 = (-5 * 2 + 3x * 2)
44 = (-10 + 6x)
Solving
44 = -10 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
44 + -6x = -10 + 6x + -6x
Combine like terms: 6x + -6x = 0
44 + -6x = -10 + 0
44 + -6x = -10
Add '-44' to each side of the equation.
44 + -44 + -6x = -10 + -44
Combine like terms: 44 + -44 = 0
0 + -6x = -10 + -44
-6x = -10 + -44
Combine like terms: -10 + -44 = -54
-6x = -54
Divide each side by '-6'.
x = 9
Simplifying
x = 9
Explanation: